Implications of Coalfield Dynamics on Associated Ecosystems: A Tangential Review - Papadkar, J. N.; Ganvir, P. S.; Nimbarte, G. R.; Patre, P. P.; Pusala, S. V.; Sakhare, S. K.; Ghagargunde, P. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Traditionally, the coal has stood as a resourceful entity for the energy demands of the society. The coalmines are the driving forces in the sufficing the energy and economy of the nation. Certainly, the existence of coal and its excavation is a much aspired endeavours for the development of any society. There are numerous prospective, functional and abandoned coalmines all over the world. Along with the intrinsic worth of the coal excavations, many studies have decisively elucidated the associated environmental complications. The ecological devastation is one of them. The ecological sphere whether it be macro or micro, is a fragile entity and must be taken care of accordingly. The process of coal excavations involves large scale landscape alteration where the entire native vegetation is removed. The ecological domain developed through an extensive period over the landscape vanishes in no time. The hydrological fluctuation also in terms of water chemistry destroys the aquatic habitat prominently known as hydroecology. The microclimatic shift is also a factor affecting drastically on the associated ecologies. The present review article strives to understand the various influencers in the coalfields dominating over the accompanying ecologies through selective endeavours executed all over the world. It also deliberates the probable measures to be taken to shield the associated ecologies in and around coalfields including the sensitization drives for protecting ecologies.